Pemanfaatan Aplikasi Deteksi Birahi Sapi Perah dan Monitoring Suhu Kandang Berbasis IoT Pada UD. Dewi Sri Desa Ranuklindungan Kecamatan Grati, Kabupaten Pasuruan - Oktriza Melfazen; Oktavia Rahayu Puspitarini; Unung Lesmanah (I-Com: Indonesian Community Journal, 2024)
The main challenges in optimising dairy farm productivity are lambing and managing barn temperature and humidity. Timely detection of lambing is key to successful reproduction. IoT-based app detects oestrus and monitors barn temperature. The system calculates the cow's fertile period and alerts the farmer for timely insemination, increasing the chances of reproductive success. IoT-connected sensors monitor barn temperature and humidity, maintaining a stable environment for the cows and increasing productivity.